CONTRIBUTION OF PLANTS AND TRADITIONAL MEDICINES TO THE DISPARITIES AND SIMILARITIES IN ACUTE POISONING INCIDENTS IN BOTSWANA, SOUTH AFRICA AND UGANDA - Malangu, Ntambwe (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Acute poisoning incidents are one of the leading causes of morbidity and hospitalization in several countries. The purpose of this analysis was to compare the patterns of acute poisoning in three countries namely, Botswana, South Africa and Uganda; and examine the similarities and disparities in the patterns of occurrence of acute poisoning based on the sociodemographic factors of the victims, the toxic agents involved, the circumstances surrounding the incidents and their outcomes. Materials and methods: This paper is based on the re-analysis of data that were collected from January to June 2005 by some Master of Public Health students using a similar data collection tool. A single dataset made of the original individual datasheets was constituted and analysed. Results: Overall, it was found that the mean age of victims of acute poisoning was 20.9 ± 14.5 years; the youngest victim was a 3 months old boy from South Africa; and the oldest was a 75 years old man from Uganda. In descending order, the most common toxic agents involved in poisoning incidents were household products (46.1%), agrochemicals (18.8%), pharmaceuticals (14.0%), animal and insect bites (13.0%), food poisoning (4.5%), as well as plants and traditional medicines (3.6%). Across the three countries, acute poisoning occurred mainly by accident, but the contextual factors of each country led to a pattern of acute poisoning that showed some similarities with regard to the distribution of deliberate self-poisoning among females, teenagers, and young adult victims. There were disparities related to the differential access to toxic agents, based on the age and gender of the victims. Of the 17 deaths reported, 2 (11.7%) were due to traditional medicines; household products were implicated in fatal outcomes in all three countries, though the extent of their involvement varied from country to country. Conclusion: Although plant and traditional medicines caused fewer cases of acute poisoning incidents, they contributed considerably to fatal outcomes.